'We are planning to leave, all of us'-a realist study of mechanisms explaining healthcare employee turnover in rural Ethiopia - Joris van de Klundert; Judith van Dongen- van den Broek; Ebrahim Mohammed Yesuf; Jasmijn Vreugdenhil; Saeid Mohammed Yimer (BMC, 2018)
Abstract Background We study healthcare employees' turnover intentions in the Afar National Regional State of Ethiopia. This rural region is experiencing the globally felt crisis in human resources, which is inhibiting its ability to meet health-related sustainable development goals. Methods Realist case study which combines literature study and qualitative analysis of interview and focus group discussion data, following a realist case study protocol. Results A large majority of employees has turnover intentions. Building on Herzberg's two-factor theory, person-environment fit theory, as well as recent sub-Saharan evidence, analysis of the collected data yields four turnover mechanisms: (1) lack of social and personal opportunities in the region, (2) dissonance between management logic and professional logic, (3) standards of service operations are hard to accept, and (4) lack of financial improvement opportunities. Conclusions While the first and fourth mechanisms may be out of reach for local (human resource) management interventions, the second and third mechanisms proposed to explain health workforce turnover appear to be amenable to local (human resource) management interventions to strengthen healthcare. These mechanisms are likely to play a role in other remote sub-Saharan regions as well.